(untitled) (Research, Society and Development, 2021)
Objective: To describe facial trauma in women who are victims of violence and the role of the Dentist-Surgeon in treating these cases. Methods: This is a narrative review study of the literature on the subject of maxillofacial trauma in women victims of physical violence. Results: The face region becomes a target because the aggressor can clearly visualize the feeling of pain, being a way to externalize the dominance over the woman, since her desire is often to depreciate her and make her submissive. It is possible to use parameters that every 4 minutes a woman is attacked, with her partners/partners being characterized as the main aggressors (65.6%), followed by ex-partners (24.2%), acquaintances (8.73%) or unknown (1.47%). Among the maxillofacial injuries resulting from violence against women, it has been reported that injuries to soft tissue on the face are the most prevalent. Conclusion: It is concluded that maxillofacial trauma due to violence in women has an expansive number, thus it is necessary to recognize the dentist in the scenario intervening in the fight against violence.